Better Body Workouts for Women - Hodgkin, Dean (Human Kinetics, 2014)
Are you serious about your workouts but disappointed in the results? Discover the best methods for assessing your current fitness level, identifying physical strengths and deficiencies, setting and refining training goals and selecting and customizing the programs to make an immediate, lasting impact.